2005
DOI: 10.1097/01.pas.0000158397.65190.9f
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Aberrations in Perineurioma

Abstract: Only two karyotypes of perineurioma have previously been reported, 46XX,del(10)(q22q24),der(10),del(22)(q11-12q?)/47, idem,+der(10) (in a sclerosing perineurioma of the finger) and 45,XX,add(14)(p13),-22,add(22)(q11.2) (in an intraneural perineurioma). We investigated the clinicopathologic and cytogenetic findings in four consecutive perineuriomas in children, including two small (< or =1 cm) digital sclerosing perineuriomas, a 2-cm intraneural perineurioma, and a 16-cm abdominal soft tissue perineurioma. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…Although initial reports suggested that no apparent association existed with either neurofibromatosis type 1 (NF1) or neurofibromatosis type 2 (NF2), [20] extraneural perineuriomas have recently been reported in patients with both disorders [21,22]. Similar to schwannoma and neurofibroma, NF2 deletions (monosomy 22) have been observed in the perineurioma including the extraneural sclerosing variant [23,24] and aberrations in chromosome 10 have been shown to be a feature of the sclerosing perineurioma in particular [25].…”
Section: Discussionmentioning
confidence: 84%
“…Although initial reports suggested that no apparent association existed with either neurofibromatosis type 1 (NF1) or neurofibromatosis type 2 (NF2), [20] extraneural perineuriomas have recently been reported in patients with both disorders [21,22]. Similar to schwannoma and neurofibroma, NF2 deletions (monosomy 22) have been observed in the perineurioma including the extraneural sclerosing variant [23,24] and aberrations in chromosome 10 have been shown to be a feature of the sclerosing perineurioma in particular [25].…”
Section: Discussionmentioning
confidence: 84%
“…Sclerosing perineuriomas occur almost exclusively in the hands of young adults, often males, and present as small, painless nodules characterized by proliferation of epithelioid and spindle cells in a trabecular or whorled pattern within a markedly dense sclerotic stroma. Interestingly, deletion of chromosome 10q is a feature of sclerosing perineuriomas [31], a genetic signature different from the chromosome 22 abnormalities often seen in conventional STP. With respect to perineuriomas, only one oral example of reticular perineurioma, a gingival tumor, has been reported [13].…”
Section: Discussionmentioning
confidence: 96%
“…Most have abnormalities of chromosome 22 [23][24][25][26][27] with deletions and point mutations of the NF2 gene on 22q11-q13.1 [25,26]. Chromosome 10q rearrangements or deletions in sclerosing perineuriomas [24,26] and a loss of chromosome 13 in extraneural soft tissue perineurioma [27] have also been reported. Our tumor has the conventional appearance of perineurioma, confirmed by positivity with EMA and claudin-1 and electron microcopic studies.…”
Section: Discussionmentioning
confidence: 98%